ANALISIS TEGANGAN DAN REGANGAN AKIBAT VARIASI NILAI KOEFISIEN GESEK PADA INTERAKSI KONTAK RING PISTON DENGAN CYLINDER LINER MENGGUNAKAN METODE ELEMEN HINGGA - Nababan, Zerry Hansnico Christian Mausi; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Cylinder liner is a component that serves to protect the inside of the engine block from direct friction with the piston ring while the piston ring itself is a component that serves to minimize the gap between the piston and the cylinder liner so that the pressure and temperature of the gas in the combustion chamber are maintained in optimal conditions. This study is to investigate how the stress and strain that occurs due to an increase in the value of the coefficient of friction on the contact interaction of the piston ring with the cylinder liner. The loading given is a pressure of 2 MPa then the coefficient of friction that occurs between cast iron and cast iron in lubricated conditions is 0.08, 0.1, and 0.12. Based on the simulation results, increasing the value of the friction coefficient has an effect on increasing the stress and strain values that occur in the cylinder liner. At a friction coefficient of 0.08 the stress that occurs in the cylinder liner is 162.76 MPa and a strain of 0.0020007 m/m. At a friction coefficient of 0.1 the stress that occurs is 163.73 MPa and a strain of 0.002006 m/m. At a friction coefficient of 0.12 the stress that occurs is 164.91 MPa and a strain of 0.0020143 m/m. Keywords: cylinder liner, piston ring, contact interaction, stress, strain